Experience of geosentetic materials use in drainage system device - Dmytriiev, Dmytro; Vasylchuk, Serhiy; Yaremchuk, Mariya; Petrоvanchuk Yulia (Academic journal Industrial Machine Building Civil Engineering, 2018)
At present, objects of responsibility (consequences) construction various classes, including SS-3 occurs in areas with possible manifestations of dangerous engineering-geological processes. One of such processes types is flooding. Based on the world experience, the main possibilities of using geosynthetic materials in various fields of construction are considered. Requirements for such materials and the conditions for their use are set out in European norms. An analysis of the program that is used to calculate drainage systems to meet force requirements in Ukraine is performed. These materials have good prospects for building in Ukraine with appropriate justification, considering the normative documents in force in our country.